Fish Farming for prosperity - Panemangalore, Arun (FARD, 2022)
This book documents the success of women groups in fish farming under the Odisha Governments flagship program "input assistance to WSHG for scientific pisciculture in GP tanks" over the last three years. This document is produced in collaboration with Fisheries and Animal Resource development department, Department of Mission Shakti, Government of Odisha.